Risk Management in Islamic Banking: The Influence of Leadership, Islamic Work Ethics, and Length of Service - Hery Wuryanto; Arif Aria Manggala; Kemal Wiranataatmadja (Journal of Economics Business Industry, 2024)
This study examines the influence of Leadership and Islamic Work Ethics on the Risk Management function at Bank Jabar Banten Syariah, with Employee Characteristics as mediating variables, aiming to identify which individual attributes condition the strength of these relationships within a regional Islamic banking institution. : A quantitative associative-descriptive design was adopted. The population comprised all BJB Syariah employees across 30 office units in West Java and Banten Province. Purposive sampling yielded 250 respondents from positions engaged in risk management functions. Structured Likert-scale questionnaires were distributed and analyzed using Partial Least Squares Structural Equation Modeling via SmartPLS. Leadership significantly influences Risk Management (β = 0.263, p = 0.011). Islamic Work Ethics showed a stronger effect (β = 0.412, p = 0.000), making it the dominant predictor. Among five employee characteristics tested as mediators, only Length of Service produced significant indirect effects on both paths (Leadership: β = 0.091, p = 0.022; Islamic Work Ethics: β = 0.083, p = 0.030). Gender, Educational Level, Conventional Banking Experience, and Age were non-significant. The model explained 50.1 percent of Risk Management variance. BJB Syariah management is encouraged to embed Islamic Work Ethics more deeply into institutional culture, emphasizing justice, the conception of work as worship, and commitment to halal income, while implementing ISO 31000 to strengthen institutional risk culture beyond formal certification programs. This study also provides evidence that religiosity-grounded Islamic ethical values carry greater explanatory power for risk management behavior than structural leadership, contributing a novel empirical perspective to Islamic banking governance literature